2015
DOI: 10.1016/j.plaphy.2015.04.001
|View full text |Cite
|
Sign up to set email alerts
|

The symbiosis between Nicotiana tabacum and the endomycorrhizal fungus Funneliformis mosseae increases the plant glutathione level and decreases leaf cadmium and root arsenic contents

Abstract: a b s t r a c tOver time, anthropogenic activities have led to severe cadmium (Cd) and arsenic (As) pollution in several environments. Plants inhabiting metal(loid)-contaminated areas should be able to sequester and detoxify these toxic elements as soon as they enter roots and leaves. We postulated here that an important role in protecting plants from excessive metal(loid) accumulation and toxicity might be played by arbuscular mycorrhizal (AM) fungi. In fact, human exploitation of plant material derived from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(14 citation statements)
references
References 52 publications
(45 reference statements)
2
9
0
1
Order By: Relevance
“…This implies the beneficial interaction with endophytic fungal enables plants to cope with oxidative stress induced by Ni toxicity. The findings of the present study are consistent with those reported by Degola et al (2015) and Wang et al (2016), who found enhanced antioxidant activities in maize and Nicotiana tabacum plants inoculated with endophytic fungi under heavy-metal stress. GSH is an important antioxidant owing to its reducing potential, which can respond directly as a free radical scavenger.…”
Section: Discussionsupporting
confidence: 93%
“…This implies the beneficial interaction with endophytic fungal enables plants to cope with oxidative stress induced by Ni toxicity. The findings of the present study are consistent with those reported by Degola et al (2015) and Wang et al (2016), who found enhanced antioxidant activities in maize and Nicotiana tabacum plants inoculated with endophytic fungi under heavy-metal stress. GSH is an important antioxidant owing to its reducing potential, which can respond directly as a free radical scavenger.…”
Section: Discussionsupporting
confidence: 93%
“…For instance, the inoculation of endophytic Sphingomonas SaMR12 increased the GSH concentration and subsequently improved Cd tolerance and accumulation in the roots of Sedum alfredii (Pan et al 2016). The endophytic F. mosseae reduced the Cd content in the leaves and roots by increasing the GSH content in tobacco plants (Degola et al 2015). In addition, the endophytic fungi colonization altered the heavy metals' distribution in the host plant.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the endophyte Sphingomonas SaMR12 up-regulates the expression of GSH synthesis-relevant genes (ATPS, GS and GSH1), increases GSH concentrations and subsequently enhances both Cd tolerance and accumulation (Pan et al 2016). Similarly, the AM fungus Funneliformis mosseae decreases leaf Cd contents with increasing GSH levels in tobacco (Degola et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The complexation of As with ligands and its vacuolar compartmentation is another mechanism of As detoxification in plants [ 6 , 50 ]. Thiol-reactive cysteine-rich peptides such as phytochelatins (PCs) and metallothioneins strongly bind with As and convert it to a non-toxic form [ 32 , 51 ].…”
Section: Introductionmentioning
confidence: 99%